2009
DOI: 10.1016/s0140-6736(09)61340-4
|View full text |Cite|
|
Sign up to set email alerts
|

Usual versus tight control of systolic blood pressure in non-diabetic patients with hypertension (Cardio-Sis): an open-label randomised trial

Abstract: Boehringer-Ingelheim, Sanofi-Aventis, Pfizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
233
0
15

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(271 citation statements)
references
References 29 publications
(38 reference statements)
12
233
0
15
Order By: Relevance
“…Importantly, no worsening of HR-QOL was documented during the study. As accumulating evidence suggests favorable effects of sufficient or intensive BP lowering treatment on pathophysiological aspects, including cardiovascular prognosis, [11][12][13][14] our results may further support such a treatment strategy from the psychosocial standpoint, possibly leading to augmentation of adherence with treatment. Recent progress in medical technology and cardiovascular pharmaceuticals has highlighted that the improvement of functional and psychosocial HR-QOL beyond a good longitudinal prognosis is needed as an aim of medical treatment.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Importantly, no worsening of HR-QOL was documented during the study. As accumulating evidence suggests favorable effects of sufficient or intensive BP lowering treatment on pathophysiological aspects, including cardiovascular prognosis, [11][12][13][14] our results may further support such a treatment strategy from the psychosocial standpoint, possibly leading to augmentation of adherence with treatment. Recent progress in medical technology and cardiovascular pharmaceuticals has highlighted that the improvement of functional and psychosocial HR-QOL beyond a good longitudinal prognosis is needed as an aim of medical treatment.…”
Section: Discussionsupporting
confidence: 62%
“…[7][8][9][10] Recent studies showed that tight pharmacologic control of systolic BP to < 130 mm Hg achieved more favorable outcomes compared with standard treatment. 11,12) Moreover, the SPLINT trial also revealed that more intensive treatment, to a systolic BP of less than 120 mm Hg, in patients without diabetes at increased risk for CVD significantly decreased rates of major cardiovascular events and death from any cause in comparison with standard treatment. 13) Thus, intensive treatment of HT is strongly required, especially in patients with a higher risk of CVD.…”
mentioning
confidence: 99%
“…Furthermore, in the Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial, the chlorthalidone group, in which BP averaged 134/76 mmHg at 4.9-year follow-up, had better CVD outcomes, particularly among black participants, compared with the other treatment groups that had less-effective BP control [21]. The Cardio-Sis study was a prospective, randomized trial in 1111 European nondiabetic men and women with SBP ‡ 150 mmHg, average age 67 years, plus one additional CVD risk factor at entry [22]. The study compared the target SBP of < 140 mmHg (usual control; n = 553) or < 130 mmHg (tight control).…”
Section: Antihypertensive Treatmentmentioning
confidence: 99%
“…Accordingly, one might expect the benefits of reducing SBP o140 mm Hg or lower, which have been shown in younger populations such as Cardio-Sis. 7 Statistical power might have been insufficient in JATOS and VALISH to detect a small difference between the groups, if present. Furthermore, targeting SBP o140 mm Hg was not associated with the increase in adverse events in JATOS and VALISH.…”
mentioning
confidence: 99%
“…a Event rates of composite cardiovascular end points are shown as those of the primary outcomes for JATOS 4,5 and VALISH, 6 and that of the secondary outcome for Cardio-Sis. 7 Commentary…”
mentioning
confidence: 99%